(untitled) (Research, Society and Development, 2022)
This article aims to analyze the implementation of a housing policy in the Marine Extractive Reserve Caeté-Taperaçu (REMCT), located in the municipality of Bragança, in the state of Pará, which allows us to observe how the precariousness of housing constructions can increase inequalities and result in developments that affect the quality of life. The Housing Credit was responsible for the construction of housing for REMCT residents from 2005 to 2013. Although it took a considerable period of time for its implementation, the public policy was not able to reach even 30% of the total number of people who were registered. Added to this are the complaints of RESEX residents about the precariousness of housing construction, without taking into account the labor and environmental needs required by the territory, mostly occupied by marine extractivists. Another reverse factor was the interruption of resources destined to INCRA, the financing body of Housing Credit, deepening the deficit in living conditions. For this qualitative analysis, a bibliographic survey was carried out on Marine Extractive Reserves, public policies, housing policies and inequality and the Amazon; semi-structured interviews were carried out with residents of the Resex; and data collection on official websites and platforms. From the results, we realize that the housing policy has an ambiguous character, on the one hand, it has produced material satisfaction among its owners, but also, by not reaching all the needy, it can contribute to the intensification of inequalities.